Take It Slow: can feedback from a smart fork reduce eating speed? - Sander Hermsen; Sander Hermsen (Frontiers in Public Health, 2015)
Background: Reductions in eating rate have been recommended as potential behavioural strategies to prevent and treat overweight [1–4]. Unfortunately, eating rate is difficult to modify, due to its highly automatic nature [5]. Training people to eat more slowly in everyday eating contexts, therefore, requires creative and engaging solutions.